2021
DOI: 10.15388/se.v1i42.528
|View full text |Cite
|
Sign up to set email alerts
|

The state of development of components of speech readiness of older preschool children with speech disorders

Abstract: The aim of the study is to investigate the formation of the components of speech readiness for school in preschool children with speech disorders. The study used research methods that allowed to experimentally investigate the development of the components of speech readiness: cognitive, motivational and emotional. It has been established that in children with speech disorders all components of speech readiness are impaired and require specific training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
1
10
0
7
Order By: Relevance
“…Scientific studies of scientists prove that the lack of neuromotor functionality, in particular, kinesthetic and kinetic hand praxis in older preschool children with logopathology delays not only physical but also intellectual [6,10,11] and speech [7,16] development. Konoplyasta [11] claimed in her scientific works that under the conditions of favorable development of the child, her sensorimotor activity is harmoniously switched into a hierarchical structure of voluntary activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientific studies of scientists prove that the lack of neuromotor functionality, in particular, kinesthetic and kinetic hand praxis in older preschool children with logopathology delays not only physical but also intellectual [6,10,11] and speech [7,16] development. Konoplyasta [11] claimed in her scientific works that under the conditions of favorable development of the child, her sensorimotor activity is harmoniously switched into a hierarchical structure of voluntary activity.…”
Section: Discussionmentioning
confidence: 99%
“…But this level was most characteristic of children with dysarthria (45.5% (n = 214)), who have weakly developed finger praxis; with a neurotic form of stuttering (15% (n = 6)), in which we note the lack of fine motor skills, the need for additional instruction, a visual sample. Preschoolers of this group did not pay attention to their motor errors, all attempts to complete the task had shortcomings: a long search for the position of joining the thumb and index fingers into a ring (they connected different fingers); difficulty moving from the position of Having uncomplicated speech disorders or their long-term correction allows children to fully perform differentiated motor exercises [10,11]. The results of the study of the performance of the task "Differentiated hand movements" showed that high scores belonged mostly to children with normotypical development (49.6% (n = 124)) and 31.4% (n = 112) with logopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ключові слова: діагностика емоцій, діти старшого дошкільного віку, емоційна грамотність, емоції, порушення мовлення. Визначені результати дослідження свідчили про важливість розвитку в дітей знань про емоції та розвиток мовленнєвих здібностей з метою покращення розуміння ними психічних станів Bielova, 2019Bielova, , 2021Helland, Posserud, Lundervold, 2020).…”
unclassified
“…Для вивчення емоцій розроблено різні діагностичні матеріали, найбільш популярними стають дослідження лицьової експресії P. (Бєлова, 2022а, 2022b. (Bielova, 2019(Bielova, , 2021Helland, Posserud, Lundervold, 2020;Ekman, 1992;Russell, 1980; Abstract. The purpose of this is to identify the current state of emotional literacy, which affects the speech readiness to study at school of older preschool children with logopathology.…”
unclassified